1997
DOI: 10.1002/(sici)1097-0290(19971105)56:3<304::aid-bit8>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Crossflow microfiltration of recombinant Escherichia coli lysates after high pressure homogenization

Abstract: Crossflow membrane filtration was used to process recombinant Escherichia coli cell lysates containing protein inclusion bodies after high pressure homogenization. The number of passes through the high pressure homogenizer changed the viscosities and average particle sizes of the cell lysates. The different cell lysates were processed with a hollow fiber unit containing microfiltration membranes and a plate and frame unit with either ultrafiltration or microfiltration membranes. There were differences in perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…This relationship is reasonable and is supported qualitatively by Forman et al, who showed that a protein exhibited a sieving coefficient higher than 90% at a very low permeation flux of 3 Lmh (39). This is also corroborated by the work of Bailey and Meagher (40). The sieving coefficient through the membrane pores is evaluated by the traditional method based on solute partitioning coefficient, solvent transport parameters, and membrane characteristics as described in Zeman and Zydney (16).…”
Section: Theoretical Backgroundsupporting
confidence: 78%
“…This relationship is reasonable and is supported qualitatively by Forman et al, who showed that a protein exhibited a sieving coefficient higher than 90% at a very low permeation flux of 3 Lmh (39). This is also corroborated by the work of Bailey and Meagher (40). The sieving coefficient through the membrane pores is evaluated by the traditional method based on solute partitioning coefficient, solvent transport parameters, and membrane characteristics as described in Zeman and Zydney (16).…”
Section: Theoretical Backgroundsupporting
confidence: 78%
“…Datar and Rosen (1987) even suggested a two-stage homogenizer or an auxillary equipment to reduce the viscosity of homogenates. However, repeated passage of cells through a homogenizer is undesirable due to the micronisation of the cell debris (Bailey and Meagher, 1997;Bailey et al, 1995;Keshavarz, 1991;Keshavarz et al, 1990) and its detrimental effect on clarification (Agerkvist and Enfors, 1990;Hutchinson et al, 2006), precipitation (Hagen et al, 1996), filtration (Lee et al, 2004;Shu-Sen, 1988;Tarleton and Wakeman, 1994), and chromatography (Grabski et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Figure shows the effect of homogenization on thawed cell broth. Homogenization at 500 bar for two passes is used as it reflects a typical process for complete cell disruption and total product release (Bailey and Maegher, ). As expected, there is a considerable shift towards smaller particle sizes with all aggregates above ∼10 µm (Fig.…”
Section: Resultsmentioning
confidence: 99%